Optimalisasi Pembelajaran Sejarah Berbasis Digital di Tingkat Sekolah Dasar - jamal, ahmad; Nazib, Fiqra; Yuliani, Farah (Jurnal Pendidikan Agama Islam, 2024)
Education is a process that takes place in life as an effort to balance inner conditions with external conditions. This balancing process is a form of survival that is carried out so that oneself can participate in every activity that takes place in life. This article aims to discuss history lessons at SDN 1 Godog which are in the subject (PAI) in which there is some material about history which is still basic and focuses on seven stages of learning, namely preparation, implementation, media and methods, curriculum, response students, problems, and learning evaluation. This research was carried out using qualitative and descriptive research, trying to study certain subjects and describe and describe these subjects. Based on the research results, history learning at SDN 1 Godog: Firstly, learning planning activities have been carried out well because they already understand curtilas and the independent curriculum. Second, the implementation of learning activities refers to the RPP. Key words: zakat mal, religious obligations, social welfare